The specificity of selected water sports and the importance of motor skills - Pankanin, Ewelina (Journal of Education, Health and Sport, 2018)
Motor abilities are human movement abilities. They characterize the level of motor skills. Athletes present a particularly high level of these abilities. It results from individual predispositions of the body as well as proper training. Each sport discipline has its own specificity and requires the athlete to develop particular skills specifically.